Filling a Geographical Gap: New Paleoecological Reconstructions From the Desert Southwest, USA - Brunelle, Andrea; Minckley, Thomas A.; Shinker, Jacqueline J.; Heyer, Josh (Frontiers in Earth Science, 2018)
In 1916 the time stamp for quantitative palynology was set with Lennart von Post's initial paper on pollen analysis and environmental change in the Scandinavian peat bogs. In the 1930s, Von Post provided a map of the known palynological reconstructions. This map showed many conspicuous gaps of geographic coverage that have endured to this day. In particular, environmental reconstruction in arid lands remain much less known, largely due to the paucity of depositional environments in these areas as well as challenges with preservation in regions either uniformly dry or subjected to strong wet/dry phases. Over the last decade we have examined linkages between desert wetland development and episodes of wet and arid conditions. Desert wetland, or ciénegas, are recharged by groundwater and appear to be sensitive to climate-driven groundwater fluctuations. These systems appear to “grow” during wet periods potentially associated with enhanced El Niño activity, suggesting an important linkage with groundwater dynamics and the quantity and frequency of winter precipitation delivery. Hydrologic conditions in ciénegas are also important controls on the preservation of pollen, where episodes of aridity coincide with periods of poor pollen preservation. We assess modern El Niño events, as analogs of past wet conditions, to provide context on the atmospheric controls for delivery of moisture into the desert southwest during winter. Our analysis shows that anomalously high and persistent moisture delivery into the region during El Niño events enables the growth of ciénegas, improves preservation of pollen and promotes the growth of fuels necessary to support wildfire. This paper examines ciénega sites located in the southwestern region of North America at the US/Mexico Border and discusses results that addresses a geographical gap identified by Von Post's original work in paleoenvironmental research.